2019
DOI: 10.1088/1755-1315/321/1/012018
|View full text |Cite
|
Sign up to set email alerts
|

Forming of minimum water content in the rivers of the Upper Don basin

Abstract: The article analyses, on the example of the river Bityug - Bobrov (Verkhniy Don, Voronezh Region), the dynamics of the absolute low water minimums of the low-water run-off. It demonstrates that, in the current century, due to the increase in summer-autumn and winter water content, the dates of absolute minimums of runoff have been shifting (rounded up to a month) for later periods of summer-autumn and earlier periods of winter low water. The highest recurrence of absolute minimums of the winter low water falls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…This characteristic is necessary when planning many water management activities (river navigation, reconstruction and reconstruction of water intake structures, operation of irrigation systems, wastewater discharge, etc.). Therefore, a large number of scientific publications have been devoted to the study of the regularities of the formation of MAD [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This characteristic is necessary when planning many water management activities (river navigation, reconstruction and reconstruction of water intake structures, operation of irrigation systems, wastewater discharge, etc.). Therefore, a large number of scientific publications have been devoted to the study of the regularities of the formation of MAD [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…In the article [5], on the example of the Bityug River (Upper Don, Voronezh region), an analysis was made of the dynamics of absolute low-water lows of low-water runoff. It is shown that in the current century, due to the increase in summer-autumn and winter water supply, the dates of absolute runoff minima shifted to later periods of summer-autumn and earlier periods of winter low water.…”
Section: Introductionmentioning
confidence: 99%